Preconcentrations of Pb(II), Ni(II) and Zn(II) by solid phase bio-extractor using thermophilic Bacillus subtilis loaded multiwalled carbon nanotube biosorbent. (March 2023) - Ozdemir, Sadin; Dündar, Abdurrahman; Dizge, Nadir; Kılınç, Ersin; Balakrishnan, Deepanraj; Prasad, Kashi Sai; Senthilkumar, Natarajan
Abstract: An alternative biotechnological solid phase bio-extraction (SPE) method was developed. Bacillus subtilis loaded multiwalled carbon nanotube was designed and used as biosorbent for the preconcentrations of Pb(II), Ni(II), and Zn(II). The experimental parameters such as sample flow rate, pH of sample solution, amounts of Bacillus subtilis and multiwalled carbon nanotube, volume of sample solution and reusability of column which affects the analytical characteristics of the SPE method were investigated in details. Surface structures were examined by using FTIR, SEM. The best pH was determined as 5.0 and the percentages recoveries of Zn(II), Ni(II), and Pb(II) were determined as 99.1%, 98.7%, and 96.2%, respectively, at a flow rate of 3 mL/min. In this study, in which the profitable sample volume was determined as 400 mL and the amount of multiwalled carbon nanotube (MWCNT) as 50 mg. It was also observed that the column had a significant potential to preconcentrate Zn(II), Ni(II), and Pb(II) even after 25 reuses. The biosorption capacities for Zn(II), Ni(II) and Pb(II) were calculated as 39.67 mg/g, 45.98 mg/g and 51.34 mg/g respectively. The LOD values were calculated as 0.024 ng/mL for Pb(II), 0.029 ng/mL for Ni(II), and 0.019 ng/mL for Zn(II). The linear range was detected as 0.25–25 ng/mL. The concentrations of Pb(II), Ni(II), and Zn(II) in a variety of real food samples were determined by using developed method after application of certified reference sample. Graphical abstract: Image 1 Highlights: Solid phase bio-extraction method was developed using B. subtilis loaded MWCNT. The biosorbent was used for the preconcentrations of Pb(II), Ni(II), and Zn(II). Zn(II), Ni(II), and Pb(II) were recovered as 99.1%, 98.7%, and 96.2%, respectively. The column was used even after 25 reuses to preconcentrate Zn(II), Ni(II), and Pb(II).